The expression of estrogen receptors during the Mytilus galloprovincialis ovarian cycle. Issue 7 (30th May 2019) - Agnese, Marisa; Rosati, Luigi; Prisco, Marina; Borzacchiello, Luigi; Abagnale, Ludovico; Andreuccetti, Piero
Abstract: The aim of this paper is to assess, by real‐time polymerase chain reaction and in situ hybridization, the expression of estrogen receptors ER1 and ER2 during the ovarian cycle of Mytilus galloprovincialis . By considering four phases of the reproductive cycle, that is stasis and previtellogenic stage (Stage 0), early vitellogenesis (Stage I), vitellogenesis (Stage II), full‐grown oocyte (Stage III), our investigation demonstrates that the two receptors are differently expressed during the phases investigated of the ovarian cycle: ER1 reaches the highest level at Stage III, whereas ER2 reaches the highest level at Stage II, with ER2 always present at higher levels than ER1. The stage‐dependent receptor expression was recorded within oocytes, follicle cells, and adipogranular cells. No ER1 and ER2 messenger RNAs (mRNAs) were found within vesicular cells. It is to be noted that the ER1 and ER2 expression within the growing oocytes, the follicular, and adipogranular cells overlaps with that of the mRNA for vitellogenin in the same cells, strongly suggesting that in Mytilus, as in vertebrates studied so far, the vitellogenin expression is under the control of estrogens. Abstract : Real‐time polymerase chain reaction for ER1 and ER2 messenger RNA (mRNA) in different phases of ovarian cycle of Mytilus galloprovincialis . 18S mRNA was used as an endogenous reference gene. ER1 and ER2 mRNA showed cyclic trends. Note that the highest level of ER1 mRNA is recorded in Stage III, whereas the lowest one in Stage 0. Differently, the highest level of ER2 mRNA is recorded in Stage II, whereas the lowest one in Stage 0. Different letters correspond to statistically significant differences ( p < 0.05). Research Highlights: The aim of this paper is to assess, by real‐time polymerase chain reaction and in situ hybridization, the expression of estrogen receptors ER1 and ER2 during the ovarian cycle of Mytilus galloprovincialis We demonstrated that the two receptors are differently expressed during the phases investigated of the ovarian cycle: ER1 reaches the highest level at Stage III (full‐grown oocyte), whereas ER2 reaches the highest level at Stage II (vitellogenesis), with ER2 always present at higher levels than ER1.